Teasing out cultural values embedded in reading texts used for assessment - Chan, Swee Heng; Abdullah, Ain Nadzimah; Wong, Jackson Kok Ming (Penerbit Universiti Pertahanan Nasional Malaysia, 2012)
Language can be said to be a central ideological organising principle around which contemporary human beings form mental collectivities. These mental collectivities reflect cultural values that can be imbibed through readings of issues that might be of current interest. The issues are often captured in texts that can be adopted for testing purposes to illustrate the significance of cultural values that are deemed worthy of highlight. In this context, these ‘worthy’ values are examined in a 5-year collection of SPM (Sijil Pelajaran Malaysia) Bahasa Malaysia language test papers. Cultural values reflected in the reading texts in these tests are annotated against a list of values that are embedded in connections made between language and culture. Bahasa Malaysia today is recognised as a heritage language for Malaysia and is an important tool for formalising and propagating values of an integrated society. An examination of the language experience organised through a principled learning approach (selected reading texts used for assessment) will help to inform on the tangibles of the underlying cultural values that are beholden to aspirations of a nation. The nation is empowered to propagate and maintain significant cultural values of society. The examination organises data collection through content analysis of the reading texts so as to tease out the salient cultural elements within the text.